MOTIF PENGGUNAAN FITUR EMOTICON DI MEDIA SOSIAL WHATSAPP: Studi terhadap Mahasiswa Program Studi Komunikasi dan Penyiaran Islam IAIN Madura - Siti Mariyam (An-Nida : Jurnal Komunikasi Islam, 2021)
Technological advances have indirectly shifted the pattern of community communication. Communication that is usually done by meeting each other and talking directly, can now be done without having to meet with the presence of a media (intermediary) communication. Among many communication media, whatsapp is the favorite social media for smartphone users. The trend of using emoticon features in text-based communication on WhatsApp social media is an interesting new phenomenon to study. The purpose of this study was to find out the motives that encourage using the emoticon feature, as well as the meaning of the presence of the emoticon feature on WhatsApp social media for students of the Islamic Communication and Broadcasting Study Program IAIN Madura. This study uses a type of phenomenological research which is part of a qualitative research approach. The phenomenological method aims to find out the phenomena experienced both in awareness, thought, and action. The results showed that the motive underlying the use of the emoticon feature in WhatsApp social media was to reduce misperceptions, implement feelings or expressions, and to increase intimacy. From all these motives, they fall into the category of sociogenetic motives. The presence of the emoticon feature in WhatsApp social media gives a very meaningful meaning because it can replace the presence of messages or nonverbal communication in text-based communication.